Co-developing a framework and indicators for assessing the performance of biodiversity enhancing practices - Zhang, Xin; Komarek, Adam; Zhang, Wei; Castellano, Michael (2022)
Xin Zhang, Adam Komarek, Wei Zhang, Michael Castellano WEBINAR Enhancing Biodiversity and Resilience in Intensive Farming Systems: Results from an ETH Zürich-IFPRI Collaborative study Co-organized by IFPRI, ETH Zürich, and Bayer DEC 6, 2022 - 10:00 TO 11:30AM EST